Post-infective glomerulonephritis in children: a hospital based study - Shah, Ganesh (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Post-infective glomerulonephritis (PIGN) is a common pediatric kidney disease in developing countries. This hospital based study aim to analyze clinical profile of PIGN in children in local scenario. Methods: This was a descriptive review of medical records of children admitted with a diagnosis of PIGN at Patan Hospital in three years period during 2013 to 2016. Hospital medical records were reviewed for demographic profiles, clinical features, laboratory data, treatment, and complications. The data was analyzed descriptively for frequencies and percentage values. Results: Out of 41 children with PIGN, 40 (97%) were between 5 to 15 years of age (mean 9.5), male to female ratio 1.7:1. Swelling of face and or leg and hypertension were seen in all, hypocomplementemia in 35 (85%), elevated ASO titer in 27 (66%), microscopic hematuria in 37 (90%). The complications of congestive cardiac failure were seen in five (12%), acute renal failure in four (10%) and hypertensive encephalopathy in two (5%). Conclusions: The common clinical and biochemical profile in children with PIGN were pedal edema, hypertension, hematuria and hypocomplementemia.